Modelling and Simulation of Co-Gasification of Chlorella Vulgaris and High-density Polyethylene Using Aspen Plus - Mustapha, Sherif Ishola; Adewole, Tunmise Latifat; Mohammed, Ishaq Alhassan; Aderibigbe, Fatai Alade; Yahaya, Suleiman Abimbola; Aliyu, Usman Mohammed (ABUAD Journal of Engineering Research and Development (AJERD), 2024)
A technical innovation that holds promise for producing renewable fuel and decreasing waste disposal is the production of syngas from the co-gasification of waste materials and biomass. In this present study, a new simulation model for co-gasifying high-density polyethylene (HDPE) and microalgae using Aspen plus V10 was built. Several operating parameters, including operating temperature, air equivalence ratio (ER), biomass blending ratio, steam-to-biomass ratio (S/B), and air/steam ratio, were investigated for their influence on the yield and composition of H2, CO, CO2, and CH4. Results indicated that these operating parameters had significant impacts on the gaseous products. High gasifier temperatures (1000°C) for the co-gasification process favored the formation of H2 and CO and increased their yields. Also, the yield of H2 significantly decreased when the value of the equivalence ratio was increased. According to simulation results, increasing the steam-to-biomass ratio favored the synthesis of H2 and CO up to a point. In addition, waste plastic (HDPE) in the feedstock should be kept at a minimum to favor the production of hydrogen-rich gas. The findings show that the model results agree with previous experimental studies. This research study has proven the air-steam co-gasification of microalgae and HDPE as a suitable process for the production of syngas rich in hydrogen.